Broadband Terahertz Circular‐Polarization Beam Splitter. Issue 3 (22nd December 2017) - Lee, Wendy S. L.; Nirantar, Shruti; Headland, Daniel; Bhaskaran, Madhu; Sriram, Sharath; Fumeaux, Christophe; Withayachumnankul, Withawat
Abstract: Splitting circularly polarized waves is desirable for high‐data‐rate wireless communications and study of molecular chirality at terahertz frequencies. Typically, this functionality is achieved using bulk optical systems with limitations in material availability, bandwidth, and efficiency. As an alternative, metasurfaces with spatially varying broadband birefringence are employed to attain the same functionality. It is demonstrated that a metasurface designed with gradually rotated birefringent resonators can deflect normally incident left‐handed circularly polarized and right‐handed circularly polarized waves into different directions. This beam splitting functionality is maintained over an experimentally demonstrated relative deflection bandwidth of 53%, namely, covering the band of 0.58–1.00 THz. Abstract : The fabricated metasurface consisting of metallic coaxial disk‐ring resonators is capable of deflecting normally incident left‐ and right‐handed circularly polarized waves into opposite directions. Furthermore, this beam splitting capability is preserved over a broadband range and is highly efficient. Potential applications include polarization multiplexing in terahertz communications and analyzing the response of chiral molecules.